STUDY ON BEHAVIOR INTENSION IN POINT COFFEE CONSUMERS IN THE CITY OF SEMARANG - VENDIX CHRISTO DEWA S; I MADE SUKRESNA (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine and analyze the effect of place atmosphere on behavioral intentions with the mediating effect of service quality and food quality at Point Coffee Semarang. The data source used in this research is primary data. The sampling technique is non-probability sampling with the type of convenience sampling. The level measurement used is the interval level. This research was processed using Structural Equation Modeling (SEM) with the help of AMOS 22 software. The results showed that the atmosphere had a positive effect on service quality and food quality, service quality and food quality also had a positive effect on behavioral intentions, and atmosphere had a positive effect on behavioral intentions. The atmosphere also has a positive effect on behavioral intentions through the mediation of service quality and food quality. The role of service quality and food quality is a partial mediator. Keywords: Atmosphere of Place, Quality of Service, Quality of Food, Intention of Behavior